A Systematic Review of Life Satisfaction Experiences Among Childfree Adults. (January 2023) - Stahnke, Brittany; Cooley, Morgan E.; Blackstone, Amy
Demographic trends in parenthood have revealed that more people are living their lives without children. Societal assumption, however, is that the childfree life is lacking in fulfillment. Understanding whether there is an association between being childfree and life satisfaction may provide relevant information on how to better support individuals who do not have children. Although there are many studies with the purpose of examining childlessness and some measure of general well-being, this review synthesizes such scholarship examining life satisfaction of persons without children. This review assessed published peer-reviewed articles in six social science databases (Social Science Premium, PubMed, PsycInfo, SearchWise, Google Scholar, and SagePub) between 1979 and 2020 and identified 15 articles for inclusion. Examining childfree persons, the results of this review indicate a positive association between childlessness and life satisfaction. The results of this review support the need for greater exploration of the context of life satisfaction among diverse groups of childfree older adults.